IDIOPATHIC LOBULAR PANNICULITIS IN RHEUMATOLOGY PRACTICE: THE AUTHORS’ OWN DATA - O. N. Egorova; B. S. Belov; S. I. Glukhova; S. G. Radenska-Lopovok (Научно-практическая ревматология)
Idiopathic lobular panniculitis (ILP) (synonym: Weber-Christian panniculitis) is the least studied disease in the group of systemic connective tissue lesions and characterized by systemic damage to subcutaneous adipose tissue (SAT). There is no unified concept of the etiology and pathogenesis of ILP now. The literature contains almost no data on the diagnostic value of laboratory studies and therapeutic approaches, which served as the basis for this investigation. Objective: to investigate the relationship between the clinical presentation of ILP and immune inflammatory parameters in patients with this disease.Subjects and methods. Examinations were made in 67 patients (9 men and 58 women) aged 20 to 76 years with a verified diagnosis of ILP (median duration, 78.91 [48; 540] months), who were followed up at the V.A. Nasonova Research Institute of Rheumatology for the period 2007 to 2017. The determination of α1-antitrypsin titer, liver fractions, amylase, lipase, trypsin, ferritin, creatine phosphokinase, leptin, and tumor necrosis factor-α (TNFα), chest computed tomography, and induration morphological examination were done in addition to physical examination.Results and discussion. The disease was found in all age groups, but it accounted for more than half (57%) of cases at the most able-bodied age (45–60 years). Analysis of the clinical manifestations of ILP could identify its four types: nodular (n=30), plaque (n=10), infiltrative (n= 5), and mesenteric (n=12), which were characterized by typical clinical features. The observed group showed a significant increase in erythrocyte sedimentation rate (ESR) (p=0.01) and C-reactive protein (CRP) level (p < 0.0001). ESR correlated with tenderness on the visual analogue scale (VAS) (p<0.05; r=0.29), induration area (p<0.05; r=0.50), and rises in body temperature (p<0.05; r=0.68) and CRP level (p<0.05; r=0.68). The concentration of CRP correlated with tenderness on visual analog scale (p<0.05; r=0.46), induration area (p<0.05; r=0.61), node stage (p<0.05; r=0.41), and TNF-α concentrations (p<0.05; r=0.32). The latter showed a direct correlation with node stage (p<0.05; r=0.41) and leptin levels (p<0.05; r=0.28) and an inverse correlation with the number of nodes (p<0.05; r=-0.24). Leptin levels were increased in 35 (52.23%) patients and displayed a direct correlation with body mass index (p<0.05; r=0.46), induration area (p<0.05; r=0.31), CRP level (p<0.05; r=0.36) and an inverse correlation with the number of nodes (p≤0.05; r=-0.33). Morphological examination of skin and SAT biopsy specimens was performed in 65 (97.01%) patients. Pre- and retroperitoneal adipose tissues were biopsied in three of five patients without skin and SAT lesions; this was not done in the remaining patients because of access difficulties. ILP was verified in all cases. Therapy was performed using the essential drugs adopted in rheumatology practice. Their therapeutic effects were noted in 62.68% of cases; inefficiency and health deterioration were detected in 12 (17.91%) patients, which necessitated an increase in the dose of disease-modifying antirheumatic drugs. Seven patients were given the following biological agents: abatacept (n=2), adalimumab (n = 3), etanercept (n=1), and rituximab (n=1).Conclusion. There is an obvious need to expand knowledge about this pathology amongst physicians and to conduct further investigation in order to timely diagnose and search for the most effective treatment options for ILP.